Phylogenetic and Functional Substrate Specificity for Endolithic Microbial Communities in Hyper-Arid Environments - Crits-Christoph, Alexander; Robinson, Courtney K.; Ma, Bing; Ravel, Jacques; Wierzchos, Jacek; Ascaso, Carmen; Artieda, Octavio; Souza-Egipsy, Virginia; Casero, M. Cristina; DiRuggiero, Jocelyne (Frontiers in Microbiology, 2016)
Under extreme water deficit, endolithic (inside rock) microbial ecosystems are considered environmental refuges for life in cold and hot deserts, yet their diversity and functional adaptations remain vastly unexplored. The metagenomic analyses of the communities from two rock substrates, calcite and ignimbrite, revealed that they were dominated by Cyanobacteria, Actinobacteria, and Chloroflexi. The relative distribution of major phyla was significantly different between the two substrates and biodiversity estimates, from 16S rRNA gene sequences and from the metagenomic data, all pointed to a higher taxonomic diversity in the calcite community. While both endolithic communities showed adaptations to extreme aridity and to the rock habitat, their functional capabilities revealed significant differences. ABC transporters and pathways for osmoregulation were more diverse in the calcite chasmoendolithic community. In contrast, the ignimbrite cryptoendolithic community was enriched in pathways for secondary metabolites, such as non-ribosomal peptides (NRP) and polyketides (PK). Assemblies of the metagenome data produced population genomes for the major phyla found in both communities and revealed a greater diversity of Cyanobacteria population genomes for the calcite substrate. Draft genomes of the dominant Cyanobacteria in each community were constructed with more than 93% estimated completeness. The two annotated proteomes shared 64% amino acid identity and a significantly higher number of genes involved in iron update, and NRPS gene clusters, were found in the draft genomes from the ignimbrite. Both the community-wide and genome-specific differences may be related to higher water availability and the colonization of large fissures and cracks in the calcite in contrast to a harsh competition for colonization space and nutrient resources in the narrow pores of the ignimbrite. Together, these results indicated that the habitable architecture of both lithic substrates- chasmoendolithic versus cryptoendolithic - might be an essential element in determining the colonization and the diversity of the microbial communities in endolithic substrates at the dry limit for life.